The island edge of America : a political history of Hawai'i - Coffman, Tom (University of Hawai'i Press, 2003)
In his most challenging work to date, journalist and author Tom Coffman offers readers a new and much-needed political narrative of twentieth-century Hawaii. The Island Edge of America reinterprets the major events leading up to and following statehood in 1959: U.S. annexation of the Hawaiian kingdom, the wartime crisis of the Japanese-American community, postwar labor organization, the Cold War, the development of Hawaii's legendary Democratic Party, the rise of native Hawaiian nationalism. His account weaves together the threads of multicultural and transnational forces that have shaped the Islands for more than a century, looking beyond the Hawaii carefully packaged for the tourist to the Hawaii of complex and conflicting identities--independent kingdom, overseas colony, U.S. state, indigenous nation--a wonderfully rich, diverse, and at times troubled place. With a sure grasp of political history and culture based on decades of firsthand archival research, Tom Coffman takes Hawaii's story into the twentieth century and in the process sheds new light on America's island edge.